Treatment-limiting renal tubulopathy in patients treated with tenofovir disoproxil fumarate. Issue 5 (May 2017) - Hamzah, L.; Jose, S.; Booth, J.W.; Hegazi, A.; Rayment, M.; Bailey, A.; Williams, D.I.; Hendry, B.M.; Hay, P.; Jones, R.; Levy, J.B.; Chadwick, D.R.; et al.
Summary: Objectives: Tenofovir disoproxil fumarate (TDF) is widely used in the treatment or prevention of HIV and hepatitis B infection. TDF may cause renal tubulopathy in a small proportion of recipients. We aimed to study the risk factors for developing severe renal tubulopathy. Methods: We conducted an observational cohort study with retrospective identification of cases of treatment-limiting tubulopathy during TDF exposure. We used multivariate Poisson regression analysis to identify risk factors for tubulopathy, and mixed effects models to analyse adjusted estimated glomerular filtration rate (eGFR) slopes. Results: Between October 2002 and June 2013, 60 (0.4%) of 15, 983 patients who had received TDF developed tubulopathy after a median exposure of 44.1 (IQR 20.4, 64.4) months. Tubulopathy cases were predominantly male (92%), of white ethnicity (93%), and exposed to antiretroviral regimens that contained boosted protease inhibitors (PI, 90%). In multivariate analysis, age, ethnicity, CD4 cell count and use of didanosine or PI were significantly associated with tubulopathy. Tubulopathy cases experienced significantly greater eGFR decline while receiving TDF than the comparator group (−6.60 [−7.70, −5.50] vs. −0.34 [−0.43, −0.26] mL/min/1.73 m 2 /year, p < 0.0001). Conclusions: Older age, white ethnicity, immunodeficiency and co-administration of ddI and PI were risk factors for tubulopathy in patients who received TDF-containing antiretroviral therapy. The presence of rapid eGFR decline identified TDF recipients at increased risk of tubulopathy. Highlights: Severe renal proximal tubulopathy (Fanconi syndrome) was only rarely seen with tenofovir (TDF) exposure. Being an older, white male with advanced HIV with concomitant use of protease inhibitors or didanosine increased the risk of developing severe tubulopathy. Rapid eGFR decline or CKD often preceded tubulopapthy and if detected should prompt careful monitoring or a switch from TDF.